Concrete repair with geopolymeric mortars: influence of mortars composition on their workability and mechanical strength - Moura, D. (2011)
Since geopolymeric binders generates 70-80% less carbon dioxide than Portland cement these materials have been receiving increased attention, due to the need of reducing green house gas emissions generated by Portland cement and also to the need of new binders with enhanced durability performance. Several authors have report placement difficulties related to the low workability of geopolymeric mortars. Therefore, the purpose of this paper is to understand how their composition influences its workability and its mechanical strength. This study has investigated the joint effect of several factors on the workability and mechanical strength of geopolymeric metakaolin based mortars. The factors analyzed through a laboratory experiment of 432 specimens, and of 48 different mortar mixes were, sodium hydroxide concentration (10M, 12M, 14M, 16M), the superplasticizer content (1%, 2%, 3%) and the percentage substitution of metakaolin by calcium hydroxide in the mixture (5%, 10%). The results show that the workability decreases with the concentration of sodium hydroxide and increases with the amount of calcium hydroxide and superplasticizer. The results also show that the use of 3% of superplasticizer, combined with a calcium hydroxide content of 10%, allows improving the mortar flow from less than 50% to over 90%, while maintaining a high compressive and flexural strength.